A comparison of native and non-urate Total Antioxidant Capacity of fasting plasma and saliva among middle-aged and older subjects. (1st January 2018) - Gawron-Skarbek, Anna; Prymont-Przymińska, Anna; Sobczak, Agnieszka; Guligowska, Agnieszka; Kostka, Tomasz; Nowak, Dariusz; Szatko, Franciszek
ABSTRACT: Objectives: As plasma and salivary total antioxidant capacity (TAC) is mainly contributed by uric acid (UA), the present study measures non-urate TAC (Nu-TAC). The aim of the study was to correlate plasma native TAC, Nu-TAC and UA with their salivary analogues, and compare the UA contribution in both body fluids using two different methods. Methods: The study involved 55 middle-aged and older subjects (66.7 ± 4.5 years). TAC was determined simultaneously with two methods (ferric reducing ability of plasma – FRAP, 2.2-diphenyl-1-picryl-hydrazyl – DPPH and countertypes for saliva – FRAS and DPPHS test), with and without UA (native TAC and Nu-TAC, respectively). Plasma UA and salivary UA (SUA) were assessed. Results: Subjects with increased FRAP, DPPH and UA had higher FRAS, DPPHS and SUA, respectively ( P  < 0.05). Plasma Nu-TAC indices did not correlate with salivary Nu-TAC. The contribution of UA to the plasma and salivary DPPH tests was similar: 75.7 ± 10.3% and 75.2 ± 14.0%, respectively. However, the contribution of UA to FRAS was higher than that for FRAP (71.6 ± 13.9% vs. 64.0 ± 8.1%; P  < 0.001). Discussion: Our findings suggest that saliva is a good predictor for native plasma TAC but not for Nu-TAC. UA level is comparably dominant in saliva and in plasma according to DPPH, but lower in plasma according to FRAP.